Corpo como testemunha: o registro simbólico e o trauma na obesidade - Aleluia , Roseane Farias da Silva (2017)
The World Health Organization considers obesity as one of the top ten public health problems in the world and classifies it as an epidemic of multiple causes. When it comes to a phenomenon that modifies the body, it is noted that obesity highlights the premise that the subject responds with the body to the pains and frustrations of the lived, however, without neglecting the context of the current consumer society, excesses, in a frenetic daily life that well characterizes fast food chains. For psychoanalysis, the body is pulsional and subject to language. For Ferenczi, the body is the depositary of a sensory inscription when the absence of a psychic inscription. The objective of this study was to investigate the relationship between obesity and non-symbolized traumatic situations. Therefore, we take the phenomenon of obesity as a symptom, in which the excess of meat can be the demonstration of what was directed to the body for lack of a psychic elaboration. We use narrative as a means of accessing life history and obesity. Five subjects of both sexes, between 25 and 50 years old, participated in the study. The narratives collected in an interview were analyzed in light of the psychoanalytic framework and the conception of trauma for Freud and Ferenczi. From this, a relationship between obesity and trauma became evident, since in the reports presented there were always suffering-generating experiences in which it was not possible to make sense. In addition, it has been demonstrated that betting on the word, giving voice to the subject, is a possible way for the treatment of obesity as a symptom that refers to unconscious processes.